Answer:
a = 2
b = 11
c = 11
d = -2
Explanation:
![\sf \left[\begin{array}{cc}a&b\\c&d \end{array}\right] *\left[\begin{array}{ccc} 22&11&7\\ 6&-9&-15 \end{array}\right] =\left[\begin{array}{ccc} 22a+6b&11a-9b&7a-15b\\22c+6d&11c-9d&7c-15d \end{array}\right]](https://img.qammunity.org/2023/formulas/mathematics/high-school/vwrbtg5hdq89qiyuigw3ztnsvh995x1w63.png)
On comparing to right side, we get,
22a + 6b = 110
Divide the entire equation by 2
11a + 3b = 55 ------------(I)
11a - 9b = -77 -------------(II)
Subtract equation (II) from (I)
11a + 3b = 55
11a - 9b = -77
- + + {Now subtract}
12b = 132
b = 132/12
![\sf \boxed{\bf \ b = 11}](https://img.qammunity.org/2023/formulas/mathematics/high-school/f755r5zpnbu9g9flduabh4yhnt67dmqyp8.png)
Substitute the value of b in eqaution (I)
11a + 3*11 = 55
11a + 33 = 55
11a = 55 - 33
11a = 22
a = 22/11
![\sf \boxed{\bf \ a = 2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/b67bmbidzjc3cy3t5h2ujbe8y0z13pwmdm.png)
22c + 6d = 230
Divide by 2
11c + 3d = 115 -----------------(III)
11c - 9d = -139 ------------------(IV)
Subtract (IV) from (III)
11c + 3d = 115
11c - 9d = 139
- + -
12d = -24
d = -24/12
![\sf \boxed{\bf \ d = -2}](https://img.qammunity.org/2023/formulas/mathematics/high-school/xqaz8ggprxbzy2a5s9hspdeaamuwr0pew1.png)
Plugin d = - 2 in equation (III)
11c + 3*(-2) = 115
11c - 6 = 115
11c = 115 + 6
11c = 121
c = 121/11
![\sf \boxed{\bf \ c = 11}](https://img.qammunity.org/2023/formulas/mathematics/high-school/nx9l971eylzb1hk09xx8ywg97yyezof1eg.png)